Enhancing fenugreek productivity under water deficient Egyptian sandy soils: optimizing organic inputs and nutrients efficiencies - A. A. Hassan; M. M. Abd El-Azeim; A. M. Menesi; N. S. Abdelkarim; Jean Diatta; W. H. Al-Qahtani; A. Saleh; Samir A. Haddad (Scientific Reports)
Abstract Organic farming could be a promising approach as an agricultural system utilizing available organic materials without retrogradation natural resources. In this study, the effect of four levels of compost (0, 12, 18, and 24 t/ha) on fenugreek plants (Trigoneila foenum-greecum) over two seasons (2021–2022 and 2022–2023) was investigated in combination with different planting timings on a sandy soil. A randomized complete block design with three replications was used for the experiment conducted at the Agricultural Experiment and Research Centre of Minia University, Egypt. The Results showed that fertilizing fenugreek plants with compost significantly increased the vegetative growth traits such as plant height, number of branches/plants and herb biomass. The highest values of soil organic carbon (SOC), 986.3 mg kg-1, dissolved organic carbon (DOC), 21.l6 mg kg-1, dissolved organic nitrogen (DON), 9.43 mg kg-1, microbial biomass-C (59.67 mg kg-1.), -N (24.88 mg kg-1), -P (14.67 mg kg-1), net bacterial [95.3 (×105 cfu g-1)] and fungi [74.32(×104 cfu g-1)] counts were obtained with 24t/ha of compost. Enzyme activities of dehydrogenase (DH), urease and β-glucosidase (βG) increased significantly as the compost rate increased. For planting dates, the beginning of October was the optimal time for fenugreek production in April. For sandy soils with low fertility under arid conditions, organic and inorganic fertilizer use will enhance crop quality and productivity, soil health and soil organic matter build-up.